A southward range extension of the rockfish, Sebastes ventricosus (Scorpaeniformes: Scorpaenidae: Sebastinae) to Matsu Islands, Taiwan - Su, Yo; Yang, Tsungyu; Lin, Chienhsiang (Zootaxa, 2025)
The rockfish species, Sebastes ventricosus Temminck & Schlegel, 1843, previously documented in the southern Korean Peninsula and Japan, typically at latitudes above 32° N, is recorded for the first time in Matsu Islands, Lienchiang County, Taiwan (ca. 26° N). A detailed description of the single specimen, along with its sagittal otolith, is provided and compared with data from other specimens collected from the northwestern Pacific Ocean. This discovery marks the second record of the genus Sebastes in Taiwan’s EEZ and represents the fourth documented case of southward range extension for cold-water fishes to Taiwan. We suggest that further investigation is needed to understand the mechanism behind this southward movement, as it does not align with the typical warming trend that facilitates northward expansion.